Critiquing the Vocabularies of the Marketized University - Natalie Fenton; Des Freedman; Gholam Khiabany; Milly Williamson (Media Theory)
Critique is in crisis. Spaces in the university, where critique once flourished under the banner of academic freedom, have been appropriated and hollowed out of meaning. External pressures from the failed project of privatisation of higher education in the UK result in internal pressures from a marketized model of university management that sees critical thinking as branding content to influence market share, rather than relevance for (social) science. This paper considers how the deeds and vocabularies of neoliberalism and the market operate in academic institutions to shape the context in which critical scholarship takes place – a context in which alternative possibilities of what education should or could be for outside of “growth”, “choice” “value for money” and preparation for work, are becoming increasingly rarely envisioned. Simultaneously, academic institutions have appropriated some of the vocabulary of critique, hollowing it out so that it can be consumed without challenging the business objectives that now structure higher education. The thoroughgoing renaming of institutional practices and their sanctioned practice and operation in the context of the ongoing destruction of the university as a public good are tied to the new institutional practices, in an effort to pressurise those who work in higher education to accept that there is no alternative.  We consider the consequences of these practices and argue that, in this context, critical scholarship must also be tied to resistance, both to the vocabularies of the neoliberal university, as well as to its actions. Critique ought to expand our understanding of the possible while demonstrating that existing reality in academia and beyond can be contested in practice.